The second beam extraction channel for the accelerator “EPOS” - Dovbnya, A.N.; Guk, I.S.; Kononenko, S.G.; Koval’ev, G.G.; Mytsykov, A.O. (Вопросы атомной науки и техники, 2014)
It is proposed to build a new beam extraction channel at the linear technological accelerator “EPOS”. A more effective exposure of materials to be processed can be reached by rotating the beam in a vertical plane through 90 deg. In the paper the schematic diagram of the channel is presented and the field value in the dipole magnet is estimated. Results of modeling the electron motion in the channel with taking into account real beam parameters are given. The density of electron stream onto the material being irradiated is calculated.